2019
DOI: 10.5935/1518-0557.20190035
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic protocol for improvement of endometrial receptivity (PRIMER) for patients with recurrent implantation failure (RIF) - A pilot study

Abstract: Objective: To evaluate whether or not one should use a new Protocol for Endometrial Receptivity Improvement (PRIMER) based on platelet-rich plasma (PRP) and granulocyte colony-stimulation factor (G-CSF) to enhance ongoing pregnancy rates in patients with recurrent implantation failure (RIF). Methods: Women undergoing IVF/ICSI were prospectively divided into two groups: - PRIMER/RIF group (n:33): patients with RIF (defined as ≥2embryo transfers (ETs) and at least 5 morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Dieamant et al recently proposed a new therapeutic protocol to improve endometrial receptivity in which IU infusion of PRP was associated with the systemic use of G‐CSF. The authors observed similar gestational results (eg, implantation rates [IRs] and pregnancy and abortion rates) between the treated group (history of 4.0 ± 1.5 previous ETs) and an untreated group that was in its first attempt at IVF 33 …”
Section: Discussionmentioning
confidence: 83%
“…Dieamant et al recently proposed a new therapeutic protocol to improve endometrial receptivity in which IU infusion of PRP was associated with the systemic use of G‐CSF. The authors observed similar gestational results (eg, implantation rates [IRs] and pregnancy and abortion rates) between the treated group (history of 4.0 ± 1.5 previous ETs) and an untreated group that was in its first attempt at IVF 33 …”
Section: Discussionmentioning
confidence: 83%
“…Instead, in their work, F. Dieamant, L. D. Vagnini, J. B. Oliveira et al (2019) did not note a significant difference in the frequency of pregnancy between the two groups (study group, whom in the protocols of preparation for ET performed PRP of the endometrium and subcutaneous administration of granulocyte colony-stimulating factor; control group -did not undergo the above procedures) [25].…”
Section: Preparing For Prpmentioning
confidence: 95%
“…compared the effect of intrauterine infusion of PRP with systemic administration of granulocyte colony stimulating factor(G-CSF) in a sample size of 123, and they demonstrated that intrauterine infusion of PRP could significantly enhance clinical pregnancy rate in RIF patients in comparison with systemic administration of G-CSF ( 32 ). One study demonstrated the efficacy of the combined use of intrauterine PRP and subcutaneous G-CSF ( 33 ). When compared with control patients in their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycle attempt without PRP or G-CSF treatment, no statistically significant difference regarding implantation, clinical pregnancy and miscarriage rates was found between the two groups, suggesting the combined use of intrauterine PRP and subcutaneous G-CSF a potential new strategy for endometrial receptivity improvement ( 33 ).…”
Section: Clinical Evidence Of Prp On Endometrial Receptivitymentioning
confidence: 99%
“…One study demonstrated the efficacy of the combined use of intrauterine PRP and subcutaneous G-CSF ( 33 ). When compared with control patients in their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycle attempt without PRP or G-CSF treatment, no statistically significant difference regarding implantation, clinical pregnancy and miscarriage rates was found between the two groups, suggesting the combined use of intrauterine PRP and subcutaneous G-CSF a potential new strategy for endometrial receptivity improvement ( 33 ). However, another study holds opposing opinions.…”
Section: Clinical Evidence Of Prp On Endometrial Receptivitymentioning
confidence: 99%